Disability and Vulnerable Groups Inclusion in COVID-19 Policy and Planning in Sub-Sahara African Countries - Zandam, Hussaini; Sulaiman, Surajo Kamilu; Mohammad, Ashiru Hamza; Sabo, Abdulwali (GHMJ (Global Health Management Journal), 2024)
Background: The COVID-19 pandemic has caused an excess burden of disease in disabled and vulnerable populations. These populations may face an increased risk of contracting COVID-19, greater demand for services and social support, and reduced access to treatment. Despite various national and international efforts towards disability rights and inclusion, substantial gaps exist between disability rights legislation and its implementation. Aims: To assess the inclusion of people with disability and other vulnerable groups in policy and planning documents related to the COVID-19 pandemic response in sub-Sahara Africa. Methods: We conducted content analysis using the EquiFrame policy analysis tool and assessed commitment to 12 vulnerable groups and 21 core human rights in policy and planning documents related to the COVID-19 pandemic. We included documents on general pandemic response, stakeholder engagement, risk communication, and the COVID-19 vaccine from five sub-Saharan African countries, including Nigeria, South Africa, Ethiopia, Kenya, and Zambia. Results: The study highlights the varying degrees to which countries integrate disability, vulnerable groups, and other core human rights concepts into their COVID-19 health policies and planning documents. Only Kenya mentioned disability in their pandemic response plan. However, all countries have explicitly mentioned disability in their stakeholder engagement plans. Except for Kenya, all countries have included disability in their risk communication plans. Notably, South Africa and Zambia demonstrated extensive disability inclusion in their stakeholder engagement and vaccine plan. Thus, these countries have the potential for comprehensive and inclusive health policymaking. In contrast, Nigeria and Ethiopia lag, therefore highlighting areas of improvement across all policy domains. Conclusion: The findings emphasize the critical importance of not only mentioning disability and other vulnerable groups, but also ensuring the depth and quality of this inclusion. While there are positive strides in certain areas, there remains a consistent need for deeper and broader inclusion across all policy domains. Received: 10 September 2024  |  Reviewed: 16 October 2024  |  Revised: 03 November 2024  |  Accepted: 05 November 2024.